The Human Animal in Cortázar’s “Axolotl” - Cranfill, Jennifer (Border Crossing, 2024)
Rejecting rationality, space, and linear time, Julio Cortázar’s “Axolotl” is an ecocritical text that problematizes humancentric logic and refutes coloniality. Cortázar crafts uncertainty through ambiguity and constructs a shifting narrative for both the human (man) and non-human (axolotl) Latin American exiles in this posthumanistic short story that resolutely resists colonial ways of thinking and knowing.